Cystic echinococcosis - S. B. Chuelov; A. L. Rossina (LLC "Diagnostics and Vaccines", 2023)
The urgency of the problem of human echinococcosis is due to the widespread prevalence of this disease, polymorphism and the severity of clinical manifestations. The aim and result of the work is to summarize the data available in the literature on the etiology, epidemiology, clinic, diagnosis, treatment, prevention of human cystic echinococcosis. Conclusion. The causative agents of human cystic echinococcosis are E. granulosus s.s., E. canadensis, E. ortleppi. The liver and lungs are most often affected, less often other organs of the abdominal cavity, bones, brain, spinal cord, eyes, etc. Diagnostics is carried out on the basis of a complex of clinical, instrumental, serological, molecular genetic studies. Treatment includes surgical removal of cysts, percutaneous interventions, and drug therapy.